2020
DOI: 10.1044/2020_ajslp-19-00132
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Physiological Effects of the Effortful Swallow Maneuver in Adults With Normal and Disordered Swallowing

Abstract: Purpose This systematic review summarizes the biomechanical and functional effects of the effortful swallow in adults with and without dysphagia, highlighting clinical implications and future research needs. Specifically, the effects of the effortful swallow on swallowing physiology, safety, and efficiency were identified, as well as the strengths and limitations of current research. Method Recommendations specified by the Preferred Reporting Items for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…The tongue is a unique, single‐muscle organ of interdigitated muscle fibers (Takemoto, 2001) which plays essential roles in feeding and speech. The literature of the past decades presents an overwhelming need for novel protocols to evaluate irregularities in tongue function in both children and adults (Bahia & Lowell, 2020; Delaney & Arvedson, 2008). In the present work, we demonstrated how the objective and quantitative analysis of tongue motility (Elad et al, 2014) can be used to highlight differences in tongue motility during disease states, different methods of feeding, and before and after surgical interventions to improve tongue performance.…”
Section: Discussionmentioning
confidence: 99%
“…The tongue is a unique, single‐muscle organ of interdigitated muscle fibers (Takemoto, 2001) which plays essential roles in feeding and speech. The literature of the past decades presents an overwhelming need for novel protocols to evaluate irregularities in tongue function in both children and adults (Bahia & Lowell, 2020; Delaney & Arvedson, 2008). In the present work, we demonstrated how the objective and quantitative analysis of tongue motility (Elad et al, 2014) can be used to highlight differences in tongue motility during disease states, different methods of feeding, and before and after surgical interventions to improve tongue performance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to these findings, we did not detect a statistically significant difference in MBSImP component scores (#9, #11, #14) between non-effortful and effortful swallows. These results contribute to the mixed evidence base examining differences between non-effortful and effortful swallows in healthy adults [ 29 , 30 ]. It is also possible that MBSImP ratings may not be sensitive enough to detect subtle changes in swallowing physiology because the MBSImP is a somewhat subjective, ordinal rating scale with a limited range of scores.…”
Section: Discussionmentioning
confidence: 85%
“…For example, one study in healthy adults found that effortful swallows led to longer durations for temporal swallow kinematic measurements (e.g., hyoid movement duration, duration of UES opening) and increased pyriform sinus residue [ 30 ]. Other studies in healthy adults have found no differences in airway protection or swallowing efficiency between non-effortful and effortful swallows [ 29 ]. While research studies have examined differences in temporal kinematic measurements between non-effortful and effortful swallows in healthy adults, no studies have examined differences between non-effortful and effortful swallows using a clinical rating tool (e.g., MBSImP), and few researchers have investigated non-invasive or non-imaging alternatives to VF that are capable of determining whether the effortful swallow maneuver is accurately performed once a patient has been properly trained.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the frequent use of effortful swallow, its evidence base remains limited. A recent systematic review elucidated the evidence base for the effortful swallow manoeuvre and found just two high quality studies (Bahia & Lowell, 2020). Most research evaluating the impact of effortful swallowing has been conducted within healthy populations (Bahia & Lowell, 2020;Langmore & Pisegna, 2015).…”
Section: Introductionmentioning
confidence: 99%